Assessment of Nutritional Status for Identifying Nutritional Rickets in Children Less Than Five Years of Age - Sanaullah Khan, Sehar Zahid, Muhammad Anwar, Arshad Rafique, Shazia Siddique, Imran Yaseen, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the nutritional status for identifying nutritional rickets in children less than five years of age. Study design: Prospective study Place and duration of study: Department of Medicine Paediatrics, Arif Memorial Teaching Hospital Lahore from 1st April 2021 30th September 2021. Methodology: Sixty children suffering from rickets were enrolled. Blood sample 3cc was taken from each child and serum was separated by centrifugation. The serum was stored at -20°C until analysis. Biochemical tests including 25-OH vitamin D3, serum calcium and alanine phosphatase were done. The radiological imaging (X-ray) pictures completely demonstrated the rickets status. Demographical information, age, body mass index of each child was documented on a well-structured questionnaire. Food frequency charts related to vitamin D rich foods as well as calcium rich diet was used for assessing the nutritional status of children. Results: The mean age of the children was 3.5±1.9 years. The clinical symptoms of the enrolled children showed that sweating was most common symptoms in all sixty children suffering from rickets. Forty-eight percent cases were under weight and stunting was presented in 73% while wasting was observed in 23% of the cases. The radiological x ray imaging showed Cupping of the bones was presented in 51% of the cases followed by wrist widening in 24%. The food frequency results also presented similar findings in which serum calcium was observed inadequate in 86.6% of cases while ALP and vitamin D3 was inadequate in 90% and 100% of cases respectively. Conclusion: Vitamin D status of Pakistan children was very alarming as 100% of the cases was vitamin D deficient. Calcium deficiency was also significantly associated with nutritional rickets.